Organic Toxins as Tools to Understand Ion Channel Mechanisms and Structure - Luz Morales-Lazaro, Sara; Hernandez-Garcia, Enrique; Serrano-Flores, Barbara; Rosenbaum, Tamara (Current Topics in Medicinal Chemistry, 2015)
Ion channels constitute a varied class of membrane proteins with pivotal roles in cellular physiology and that are fundamental for neuronal signaling, hormone secretion and muscle contractility. Hence, it is not unanticipated that toxins from diverse organisms have evolved to modulate the activity of ion channels. For instance, animals such as cone snails, scorpions, spiders and snakes use toxins to immobilize and capture their prey by affecting ion channel function. This is a beautiful example of an evolutionary process that has led to the development of an injection apparatus from predators and to the existence of toxins with high affinity and specificity for a given target. Toxins have been used in the field of ion channel biophysics for several decades to gain insight into the gating mechanisms and the structure of ion channels. Through the use of these peptides, much has been learned about the ion conduction pathways, voltagesensing mechanisms, pore sizes, kinetics, inactivation processes, etc. This review examines an assortment of toxins that have been used to study different ion channels and describes some key findings about the structure-function relationships in these proteins through the details of the toxin-ion channel interactions.
Keywords: Voltage-gated channel